A case report of life threatening Dapsone Hypersensitivity Syndrome - Jeevangi, Santoshkumar R.; Saba, Amreen (International Journal of Basic & Clinical Pharmacology, 2017)
Dapsone is widely used for a variety of infections, immune and hypersensitivity disorders. However, the use of Dapsone may be associated with a plethora of adverse effects, the most serious being Dapsone Hypersensitivity Syndrome (DHS) wherein the patient typically presents with a triad of fever, skin eruption and internal organ involvement, that occurs during first 2 to 8 weeks of initiating the treatment. The incidence of DHS ranges from 0.5% to 3%. Here we report a case of severe life threatening Dapsone induced hypersensitivity reaction in a 21year old female who presented with high grade fever, generalized lymphadenopathy, skin rash and hepato-splenomegaly. This condition is best approached with immediate discontinuation of offending drug and prompt administration of oral or IV glucocorticoids. The case is being reported to emphasize the need for timely diagnosis and prompt treatment for successful outcome as it can cause irreversible organ damage or death if untreated early.